Post-traumatic stress disorder and associated factors among road traffic accident survivors in Sub-Saharan Africa: A systematic review and meta-analysis - Tigabu Munye Aytenew; Getasew Legas; Solomon Demis Kebede; Amare Kassaw; Biruk Demissie; Adane Birhanu Nigat; Yirgalem Abere; Demewoz Kefale; Birhanu Mengist Munie (PLoS ONE, 2025)
Introduction Road traffic accidents have become a global public health issue, especially in low- and middle-income countries (LMICs). According to the World Health Organization (WHO) Global Road Safety Report 2018, there are over 1.35 million deaths related to road traffic accidents (RTAs) annually. Although several primary studies have been conducted to determine the prevalence and associated factors of post-traumatic stress disorder (PTSD) among RTA survivors in sub-Saharan Africa (SSA), these studies have reported inconsistent findings. Therefore, this study aimed to determine the pooled prevalence and associated factors of PTSD among RTA survivors in SSA. Methods The studies were accessed through the Google Scholar, Scopus, PubMed, and Web of Science databases using search terms. Moreover, citation tracking was also performed. A random-effects DerSimonian-Laird model was used to compute the pooled prevalence of PTSD and determine associated factors among RTA survivors in SSA. Results A total of 17 primary studies with a sample size of 9,056 RTA survivors were included in the final meta-analysis. The pooled prevalence of PTSD among RTA survivors in SSA was 23.36% (95% CI: 18.36, 28.36); I2 = 96.73%; P < 0.001). Female gender [AOR = 2.33, 95% CI: 1.80, 3.01], depression symptoms [AOR = 2.96, 95% CI: 2.17, 4.03], duration since the accident (1-3 months) [AOR = 2.08, 95% CI: 1.23, 3.52], poor social support [AOR = 2.97, 95% CI: 1.09, 8.11], and substance use [AOR = 3.31, 95% CI: 1.68, 6.52] were significantly associated with PTSD. Conclusions The pooled prevalence of PTSD was low in SSA compared to studies that have been conducted outside the region. Female gender, depression symptoms, duration since the accident (1-3 months), poor social support, and substance use were the pooled independent predictors of PTSD among RTA survivors in SSA. Those RTA survivors with these identified risk factors would be screened and managed early for PTSD using pharmacological treatment and brief psychological intervention. Future researchers shall conduct further studies using different methods, including qualitative studies to identify additional predictors of PTSD among RTA survivors in SSA.